Process of a methodical approach to improve the blended learning to uphold higher education teaching and learning - Janani, T. (My University, 2021)
Currently, blended learning is trending among higher education institutions around the globe. Despite this growing interest, there is ongoing debate about the model of blended learning using in higher education teaching and learning. Selecting the most appropriate methodological approach for a blended learning is a major challenge for many teachers in higher education institutions. The main objective of this study is to develop a process of methodical approach to find effective BL model in higher education institution. Initially, a review of the literature identified the nature of the BL models and HE learning management system along with the issues of delivering the courses. The qualitative positivist and phenomenology study used with the Khan Octagonal framework as a grounded theory. A sample of 500 undergraduate students, 5 teachers and 3 administrators from University of Jaffna participated in this study. The researcher proposed a Demarcated Learning Management System to establish a well-designed and effective blended learning teaching and learning model. The process of EIDA, Evaluation, Implementation Determination, and Analysis establishes a well-defined methodology for finding BL Model to support higher education teaching and learning. It expands the knowledge regarding BL, enhancing understanding about pedagogies, and increases the satisfaction level of using BL in Higher Education. This process leads to six strategic dimensions: Pedagogy; Learning technology support and resources; Components of e-learning; Infrastructure facilities; Institutional culture and Ethics. Based on these dimensions, the process of methodical approach can be adopted in higher education institutions to achieve an effective and efficient blended learning model for their courses in the levels of students, lecturers and administrators. In future extensive research could be undertaken in all forms of pedagogical approaches in all universities with different students, teachers and administrators.
Keywords: Blended Learning; Learning Management System; Higher Education; Information Communication Technology; Pedagogy